Perancangan Website Travel Menggunakan Metode Agile - Putra Nizar Aditya; Bagus Mulyawan (Fakultas Teknologi Informasi Universitas Tarumanagara, 2025)
The design of Travel Services and Information Website at Khadijatul Kubra Tour Travel Company aims to develop a digital platform that provides information and services to prospective customers, especially for Hajj and Umrah trips. This website is designed with main features such as chatting with admin through WhatsApp Gateway and an online payment system to facilitate customer transactions. The design is done using the Agile Scrum methodology, which allows flexibility in developing features according to user needs. The expected result is a website that not only provides complete and clear information about travel services, but also facilitates interaction and booking efficiently. With additional features such as online payment, the transaction process becomes easier and safer for customers, thus supporting digital promotion and easy access to company services effectively.